Three-dimensional graphene composite material, preparation method and application thereof, and supercapacitor
By pretreating the carbon-containing precursor and optimizing high-energy beam current, combined with impregnation method to load pseudocapacitor materials, a three-dimensional graphene composite material was prepared, which solved the problem of insufficient specific capacity of supercapacitor electrode materials, and achieved high energy density and power The density is improved and the structural stability is maintained.
Patent Information
- Application Number
- CN202411317869.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-03
AI Technical Summary
The energy density and power density of supercapacitors are limited by the specific capacity of the electrode material, and traditional methods sacrifice the structural stability of the material when improving the electrochemical reaction capacity.
By pretreating the carbon-containing precursor and optimizing the skeleton structure of the graphene electrode material with high energy beam current, combined with impregnation loading pseudocapacitor materials, a three-dimensional graphene composite material was prepared to improve conductivity and ion transport capability.
It significantly improves the energy density and power density of supercapacitors while maintaining excellent cycle life characteristics, providing a new design idea for high-performance electrode materials, suitable for micro electronic devices.
Smart Images

Figure CN119252673A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitor electrode materials, and in particular to a three-dimensional graphene composite material, a preparation method and application thereof, and a supercapacitor. Background Art
[0002] With the rapid increase in energy usage, more stringent requirements are placed on the capacity and charge and discharge rate of energy storage devices. Supercapacitors are energy storage devices between energy storage batteries and capacitors, with good energy density and excellent power density. Energy storage devices derived from them have been used in some energy storage fields and are expected to replace traditional batteries as a new generation of power sources in the future. However, due to the specific capacity of supercapacitor electrode materials, the energy density of supercapacitors still has room for improvement. Therefore, controlling the electrochemical reaction of electrode materials in an ideal state is the key to further improving the performance of supercapacitors.
[0003] Porous carbon materials have been widely used in supercapacitors. Their high specific surface area provides a large number of active sites for electrolyte ions. However, commercial activated carbon usually stores energy in physical form, and the capacitance of the electrode material is limited. Traditional methods include loading metal oxides, metal hydroxides, conductive polymers, etc. to obtain high specific capacity, but this usually sacrifices the structural stability of the material to a certain extent. Therefore, a stable carbon skeleton structure is the basis for doping and modifying carbon electrode materials to improve performance.
[0004] Among many carbon materials, graphene is a six-membered ring structure in which carbon atoms are arranged in sp2 orbital hybridization, which has extremely strong stability. Extending this stable structure existing in a two-dimensional plane to a three-dimensional skeleton structure at a macroscopic scale will hopefully obtain a stable carbon skeleton structure. Compared with the layer-by-layer stacking of chemical vapor deposition, etching the carbon-containing precursor using a high-energy beam can directly realize the three-dimensional structure of graphene. However, traditional high-energy beam-induced three-dimensional graphene is usually achieved by changing the high-energy beam parameters, but few researchers have optimized the design of the three-dimensional graphene skeleton based on the thermal decomposition state of the precursor.
[0005] In order to solve the above problems, the present invention pre-treats the carbon-containing precursor and then uses a high-energy beam to in-situ optimize the skeleton structure of the graphene electrode material. The prepared graphene electrode material has excellent conductivity, ultra-high ion transmission capacity and significantly improved specific capacitance. The energy density and power density of the supercapacitor assembled by the graphene electrode are improved, and the excellent cycle life characteristics are maintained, which can meet the use requirements of microelectronic devices. The present invention provides a reference for the research of high-performance supercapacitor electrode materials, and is expected to replace commercial activated carbon materials and realize industrial production and application. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a three-dimensional graphene composite material, select an aromatic polymer with a high carbon content as a graphene precursor, and use different pre-treatment methods to design its thermal decomposition characteristics, so as to ensure that different three-dimensional graphene skeleton structures are obtained under the scanning of a high-energy beam, and the optimized three-dimensional graphene skeleton structure is determined by comparing and analyzing the resistance behavior and capacitance of the electrode material. At the same time, the three-dimensional graphene skeleton is used to anchor the pseudocapacitive material to broaden the working potential and obtain more abundant reactive active sites, providing a new design idea for high-performance supercapacitor electrode materials.
[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0008] The first object of the present invention is to provide a method for preparing a three-dimensional graphene composite material, comprising the following steps:
[0009] (1) Pre-treating the polymer film;
[0010] (2) exposing the pre-treated polymer film to a high-energy beam to obtain a three-dimensional graphene material;
[0011] (3) The pseudocapacitive material is loaded on the three-dimensional graphene material by an impregnation method;
[0012] (4) The three-dimensional graphene material loaded with the pseudocapacitive material is heat treated to obtain a three-dimensional graphene composite material.
[0013] The second object of the present invention is to provide a three-dimensional graphene composite material prepared by the aforementioned preparation method.
[0014] The third object of the present invention is to provide application of the three-dimensional graphene composite material as an electrode material.
[0015] A fourth object of the present invention is to provide a supercapacitor using the three-dimensional graphene composite material as an electrode material.
[0016] The excellent electrochemical performance of the three-dimensional graphene composite material of the present invention is achieved by pre-treatment of the polymer and stable compounding of the high pseudocapacitive material under the premise of preparing three-dimensional porous graphene by high-energy beam induction. Specifically, the optimization design of the graphene skeleton is achieved by pre-treating the polymer and regulating the graphitization process of the polymer in the process of preparing the graphene material by high-energy beam induction, and then the pseudocapacitive material is uniformly doped and distributed on the graphene skeleton by impregnation, and then the pseudocapacitive active material is uniformly compounded on the optimized graphene skeleton by heat treatment, so as to obtain a three-dimensional skeleton graphene electrode material for supercapacitors.
[0017] The beneficial effects of the present invention are:
[0018] (1) The present invention can improve the ion transport capacity in the electrolyte by optimizing the skeleton structure of the graphene material, thereby ensuring that the electrochemical reaction proceeds quickly and efficiently.
[0019] (2) The present invention can expand the stable working potential window by in-situ loading of pseudocapacitive active materials on the three-dimensional skeleton graphene material, providing a prerequisite for building a supercapacitor with high energy density.
[0020] (3) The three-dimensional graphene composite material prepared by the present invention is more continuous and stable, which can effectively improve the conductivity and crystal quality of the graphene material prepared by traditional high-energy beam induction, and is a reliable choice for the new generation of supercapacitor electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic diagram of the process of preparing a three-dimensional graphene material in Example 1;
[0022] Figure 2 This is a SEM image of the three-dimensional graphene material prepared in Example 1;
[0023] Figure 3 The CV curve of three electrodes assembled using the three-dimensional graphene material prepared in Example 1 as the working electrode in the potential range of 0 to 0.8 V;
[0024] Figure 4 The GCD curve of three electrodes assembled using the three-dimensional graphene material prepared in Example 1 as the working electrode in the potential range of 0 to 0.8 V;
[0025] Figure 5 Electronic impedance spectroscopy analysis of three electrodes assembled using the three-dimensional graphene material prepared in Example 1 as the working electrode;
[0026] Figure 6 This is a SEM image of the three-dimensional graphene & manganese oxide composite material prepared in Example 2;
[0027] Figure 7 The CV curve of the three-electrode assembled using the three-dimensional graphene & manganese oxide composite material prepared in Example 2 as the working electrode in the potential range of 0 to 1.2 V;
[0028] Figure 8 This is a SEM image of the three-dimensional graphene & iron oxide composite material prepared in Example 3;
[0029] Fig. 9 The CV curve of the three-electrode assembled by using the three-dimensional graphene & manganese oxide composite material prepared in Example 4 as the working electrode in the potential range of 0 to 1.0 V;
[0030] Fig.10 The CV curve of the three-electrode assembled using the three-dimensional graphene & manganese oxide composite material prepared in Example 5 as the working electrode in the potential range of 0 to 1.2 V;
[0031] Fig.11 This is a SEM image of the three-dimensional graphene material prepared in Comparative Example 4;
[0032] Fig.12 This is a SEM image of the three-dimensional graphene material prepared in Comparative Example 5;
[0033] Fig.13 The CV curve of three electrodes assembled using the three-dimensional graphene material prepared in Comparative Example 5 as working electrodes in the potential range of 0 to 0.8 V. DETAILED DESCRIPTION
[0034] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0035] The present invention provides a method for preparing a three-dimensional graphene composite material, comprising the following steps:
[0036] (1) Pre-treating the polymer film;
[0037] (2) exposing the pre-treated polymer film to a high-energy beam to obtain a three-dimensional graphene material;
[0038] (3) The pseudocapacitive material is loaded on the three-dimensional graphene material by an impregnation method;
[0039] (4) The three-dimensional graphene material loaded with the pseudocapacitive material is heat treated to obtain a three-dimensional graphene composite material.
[0040] In the present invention, an aromatic polymer with good thermal stability and high carbon retention rate is selected as a graphene precursor. Further, the thermal decomposition temperature of the polymer is 100-700°C, and the carbon retention rate is >20%. Preferably, the thermal decomposition temperature of the polymer is 200-500°C, and the carbon retention rate is >50%.
[0041] Furthermore, the polymer includes one or more of aromatic polymers such as polyimide, polyethersulfone, polyamic acid, phenolic resin, epoxy resin, etc., and the film-forming mode of the polymer includes two types: thermosetting and thermoplastic. In some specific embodiments, the polymer is one or more of thermosetting polyamic acid, phenolic resin, epoxy resin.
[0042] Furthermore, the preparation method of the polymer film includes one or more of the following methods: self-flow film formation, mold film formation, four-sided scraper film formation, coater coating film formation, etc. The polymer is dissolved in an organic solvent and prepared into a film by a solution film formation method. The organic solvent includes methanol, ethanol, propanol, etc.
[0043] Furthermore, the pretreatment includes preheating, prefreezing, oxygen plasma treatment, molecular structure modification, etc.
[0044] Furthermore, the high-energy beam includes one or more of gas laser, semiconductor laser, solid laser, fiber laser, ion beam, electron beam and the like.
[0045] Furthermore, the wavelength of the high-energy beam is 200nm to 10.6μm, the power is 1 to 500W, the scanning rate is 5 to 3000mm / s, and the scanning spacing is 0.05 to 5mm. In some specific embodiments, the high-energy beam is a gas laser with a wavelength of 10.6μm, a laser power of 1 to 50W, a laser scanning rate of 5 to 1000mm / s, and a laser scanning spacing of 0.1 to 1mm. The graphene array constructed by adjusting the laser spacing is conducive to the diffusion and transfer of electrolytes to a deeper depth, thereby helping to improve the volumetric specific capacity of the graphene material.
[0046] Furthermore, the pseudocapacitive material includes one or more of metal salts and conductive polymers. The metal salt includes one or more of heavy metal salts such as manganese salts, iron salts, cobalt salts, nickel salts, etc. The conductive polymer includes one or more of conductive polymers such as polyaniline, polypyrrole, polycarbazole, etc.
[0047] Furthermore, the immersion method includes one or more of ultrasonic treatment, water bath treatment, standing at room temperature, etc.
[0048] Furthermore, the heat treatment method includes one or more of flash Joule heating, tubular furnace heating, muffle furnace heating, high-energy beam scanning, etc. Specifically, the temperature of the flash Joule heating is 100-3000°C; the temperature of the tubular furnace heating is 100-1000°C; the temperature of the muffle furnace heating is 100-500°C.
[0049] The present invention provides a three-dimensional graphene composite material prepared by the aforementioned preparation method.
[0050] The present invention also provides application of the three-dimensional graphene composite material as an electrode material.
[0051] The invention provides a supercapacitor, which adopts the three-dimensional graphene composite material as an electrode material.
[0052] The technical solution of the present invention is described in detail below through specific embodiments.
[0053] Example 1
[0054] (1) 3 g of thermosetting phenolic resin powder was added to 10 mL of anhydrous ethanol and stirred at 300 r / min for 3 h on a rotary vane disperser to obtain a phenolic resin solution.
[0055] (2) Using a coater, the phenolic resin solution prepared above was evenly coated on a PET film with a thickness of 60 μm. The coating thickness was controlled to be 1000 μm. After coating, the film was placed in a vacuum oven at 50° C. and dried for 5 h to obtain a film.
[0056] (3) The dried film was placed in a -40°C freezer for 2 hours for pretreatment.
[0057] (4) Exposing the above pre-treated film to CO2 laser irradiation, the laser wavelength is 10.6 μm, the laser power is 7 W, the laser scanning rate is 50 mm / s, the laser scanning interval is 0.2 mm, the laser scanning number is 2 times, and the two scanning processes are perpendicular to each other, thereby obtaining a three-dimensional graphene material.
[0058] The three-dimensional graphene material prepared in Example 1 was used as the working electrode, the counter electrode was a platinum sheet electrode, the reference electrode was a saturated silver chloride electrode, and the electrolyte was a 1M Na2SO4 aqueous solution, and a three-electrode test system was assembled. The assembled three-electrode test system was tested using an electrochemical workstation, and the test contents included cyclic voltammetric characteristic curve test (CV), constant current charge and discharge curve test (GCD), electronic impedance spectroscopy test (EIS), and cycle stability test.
[0059] Figure 2 This is a SEM image of the three-dimensional graphene material prepared in Example 1. Figure 2 It can be seen that the stable and continuous three-dimensional skeleton structure of graphene materials can provide a basis for ion transport and electrochemical reactions.
[0060] Figure 3 The CV curve of the three-electrode assembled by using the three-dimensional graphene material prepared in Example 1 as the working electrode in the potential range of 0 to 0.8 V. Figure 3 It can be seen that the CV curves at different scan rates exhibit a good rectangular shape, showing excellent charge and discharge characteristics.
[0061] Figure 4 The GCD curve of the three-electrode assembled by using the three-dimensional graphene material prepared in Example 1 as the working electrode in the potential range of 0 to 0.8 V. Figure 4 It can be seen that at 1.0 mA / cm 2The current density is 533mF / cm 2 Area specific capacity.
[0062] Figure 5 The electronic impedance spectroscopy analysis of three electrodes assembled using the three-dimensional graphene material prepared in Example 1 as the working electrode. Figure 5 It can be seen that the ion transmission capability is excellent in the low frequency region.
[0063] Example 2
[0064] The method for preparing the three-dimensional graphene material in this embodiment is the same as that in Embodiment 1, except that steps (5) and (6) are added.
[0065] (1) 3 g of thermosetting phenolic resin powder was added to 10 mL of anhydrous ethanol and stirred at 300 r / min for 3 h on a rotary vane disperser to obtain a phenolic resin solution.
[0066] (2) Using a coater, the phenolic resin solution prepared above was evenly coated on a PET film with a thickness of 60 μm. The coating thickness was controlled to be 1000 μm. After coating, the film was placed in a vacuum oven at 50° C. and dried for 5 h to obtain a film.
[0067] (3) The dried film was placed in a -40°C freezer for 2 hours for pretreatment.
[0068] (4) Exposing the above pre-treated film to CO2 laser irradiation, the laser wavelength is 10.6 μm, the laser power is 7 W, the laser scanning rate is 50 mm / s, the laser scanning interval is 0.2 mm, the laser scanning number is 2 times, and the two scanning processes are perpendicular to each other, thereby obtaining a three-dimensional graphene material.
[0069] (5) The three-dimensional graphene material was placed in a 2 M manganese acetate solution for ultrasonic treatment with an ultrasonic power of 300 W and an ultrasonic time of 30 min.
[0070] (6) A CO2 laser was used to heat treat the three-dimensional graphene material infiltrated with manganese acetate solution, with a laser wavelength of 10.6 μm, a laser power of 2 W, a laser scanning rate of 50 mm / s, and a laser scanning interval of 0.1 mm to obtain a three-dimensional graphene & manganese oxide composite material.
[0071] The three-dimensional graphene & manganese oxide composite material prepared in Example 2 was used as the working electrode, the counter electrode was a platinum sheet electrode, the reference electrode was a saturated silver chloride electrode, and the electrolyte was a 1M Na2SO4 aqueous solution, and assembled into a three-electrode test system. The assembled three-electrode test system was tested using an electrochemical workstation, and the test contents included cyclic voltammetric characteristic curve test (CV), constant current charge and discharge curve test (GCD), electronic impedance spectroscopy test (EIS), and cycle stability test.
[0072] Figure 6 This is a SEM image of the three-dimensional graphene & manganese oxide composite material prepared in Example 2. Figure 6 It can be seen that the manganese oxide particles are uniformly attached to the three-dimensional skeleton of graphene, providing a large number of active sites for pseudocapacitive reactions.
[0073] Figure 7 The CV curve of the three-electrode assembled using the three-dimensional graphene & manganese oxide composite material prepared in Example 2 as the working electrode in the potential range of 0 to 1.2 V. Figure 7 It can be seen that compared with the 0.8V voltage window of traditional pure carbon materials, the working potential of the three electrodes can be extended to 1.2V.
[0074] Example 3
[0075] The preparation method of the three-dimensional graphene & iron oxide composite material in this embodiment is the same as that in Example 2, except that the 2M manganese acetate solution is replaced with a 1.5M ferric chloride solution.
[0076] Figure 8 This is a SEM image of the three-dimensional graphene & iron oxide composite material prepared in Example 3. Figure 8 It can be seen that the iron oxide is uniformly dispersed on the three-dimensional skeleton of graphene, which can provide a large amount of reversible pseudocapacitive reaction for the electrode during charging and discharging.
[0077] Example 4
[0078] The preparation method of the three-dimensional graphene & manganese oxide composite material in this embodiment is the same as that in Example 2, except that the thermosetting phenolic resin powder is replaced with thermosetting polyamic acid.
[0079] Fig. 9 The CV curve of the three-electrode assembled using the three-dimensional graphene & manganese oxide composite material prepared in Example 4 as the working electrode in the potential range of 0 to 1.0 V. Fig. 9 It can be seen that compared with the voltage window of 0.8V of traditional pure carbon materials, the working potential of the three electrodes can also be effectively expanded.
[0080] Example 5
[0081] The preparation method of the three-dimensional graphene & manganese oxide composite material in this embodiment is the same as that in Example 2, except that the pretreatment is replaced by heating treatment instead of freezing, the heating temperature is 200° C., and the heating time is 3 h.
[0082] Fig.10 The CV curve of the three-electrode assembled using the three-dimensional graphene & manganese oxide composite material prepared in Example 5 as the working electrode in the potential range of 0 to 1.2 V. Fig.10 It can be seen that the working potential of the three electrodes can also be effectively expanded, and shows excellent cyclic voltammetric characteristics.
[0083] Comparative Example 1
[0084] The preparation method of the three-dimensional graphene material in this comparative example is the same as that in Example 1, except that the freezing temperature of the film pretreatment is set to -80°C.
[0085] Fig.11 This is a SEM image of the three-dimensional graphene material prepared in Comparative Example 4. Fig.11 It can be seen that as the freezing temperature decreases, the skeleton structure units on the surface of three-dimensional graphene become more independent, which proves that the three-dimensional skeleton structure of graphene can be regulated by freezing treatment.
[0086] Comparative Example 2
[0087] The preparation method of the three-dimensional graphene material in this comparative example is the same as that in Example 1, except that the film is not subjected to freezing treatment.
[0088] Fig.12 This is a SEM image of the three-dimensional graphene material prepared in Comparative Example 2. Fig.12 It can be seen that more pores appear on the surface of graphene prepared without freezing treatment, which is related to the instantaneous thermal decomposition of the graphene precursor film.
[0089] Fig.13 The CV curve of the three-electrode assembled by using the three-dimensional graphene material prepared in Comparative Example 5 as the working electrode in the potential range of 0 to 0.8 V. Figure 3 compared to, Fig.13 The peak current of the CV curve is significantly reduced, which is related to the obstruction of ion transmission caused by pore blockage, but the CV curve also maintains good cyclic charge and discharge characteristics. Therefore, freezing the graphene precursor film can improve its thermal decomposition process under high-energy beam current, thereby obtaining a more stable and continuous three-dimensional skeleton graphene material, ensuring more sufficient electrochemical site energy storage reaction.
[0090] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a three-dimensional graphene composite material, characterized in that: The preparation method comprises the following steps: (1) Pre-treating the polymer film; (2) exposing the pre-treated polymer film to a high-energy beam to obtain a three-dimensional graphene material; (3) The pseudocapacitive material is loaded on the three-dimensional graphene material by an impregnation method; (4) The three-dimensional graphene material loaded with the pseudocapacitive material is heat treated to obtain a three-dimensional graphene composite material.
2. The preparation method according to claim 1, characterized in that: The thermal decomposition temperature of the polymer is 100-700°C, and the carbon retention rate is >20%; Preferably, the thermal decomposition temperature of the polymer is 200-500° C., and the carbon retention rate is >50%.
3. The preparation method according to claim 1, characterized in that: The polymer includes one or more of polyimide, polyethersulfone, polyamic acid, phenolic resin, and epoxy resin, and the film-forming mode of the polymer includes two types: thermosetting type and thermoplastic type; Preferably, the polymer is one or more of thermosetting polyamic acid, phenolic resin, and epoxy resin; Preferably, the polymer film is prepared by one or more of self-flowing film forming, die film forming, four-sided scraper film forming, and coater coating film forming.
4. The preparation method according to claim 1, characterized in that: The pretreatment includes one or more of preheating, prefreezing, oxygen plasma treatment, and molecular structure modification.
5. The preparation method according to claim 1, characterized in that: The high energy beam includes one or more of gas laser, semiconductor laser, solid laser, fiber laser, ion beam and electron beam; Preferably, the wavelength of the high-energy beam is 200 nm to 10.6 μm, the power is 1 to 500 W, the scanning rate is 5 to 3000 mm / s, and the scanning interval is 0.05 to 5 mm.
6. The preparation method according to claim 1, characterized in that: The pseudocapacitive material includes one or more of metal salts and conductive polymers; Preferably, the metal salt includes one or more of manganese salt, iron salt, cobalt salt and nickel salt; Preferably, the conductive polymer includes one or more of polyaniline, polypyrrole, and polycarbazole; Preferably, the immersion method includes one or more of ultrasonic treatment, water bath treatment, and standing at room temperature.
7. The preparation method according to claim 1, characterized in that: The heat treatment method includes one or more of flash Joule heating, tubular furnace heating, muffle furnace heating, and high-energy beam scanning; Preferably, the temperature of the flash Joule heat is 100-3000°C; the temperature of the tubular furnace heating is 100-1000°C; the temperature of the muffle furnace heating is 100-500°C.
8. A three-dimensional graphene composite material prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the three-dimensional graphene composite material according to claim 8 as an electrode material.
10. A supercapacitor, characterized in that: The three-dimensional graphene composite material according to claim 8 is used as an electrode material.
